Dual Endothelin-A/Endothelin-B Receptor Blockade and Cardiac Remodeling in Heart Failure With Preserved Ejection Fraction. (November 2016) - Valero-Munoz, Maria; Li, Shanpeng; Wilson, Richard M.; Boldbaatar, Batbold; Iglarz, Marc; Sam, Flora
Abstract : Background—: Despite the increasing prevalence of heart failure with preserved ejection fraction (HFpEF) in humans, there remains no evidence-based therapies for HFpEF. Endothelin-1 (ET-1) antagonists are a possibility because elevated ET-1 levels are associated with adverse cardiovascular effects, such as arterial and pulmonary vasoconstriction, impaired left ventricular (LV) relaxation, and stimulation of LV hypertrophy. LV hypertrophy is a common phenotype in HFpEF, particularly when associated with hypertension. Methods and Results—: In the present study, we found that ET-1 levels were significantly elevated in patients with chronic stable HFpEF. We then sought to investigate the effects of chronic macitentan, a dual ET-A/ET-B receptor antagonist, on cardiac structure and function in a murine model of HFpEF induced by chronic aldosterone infusion. Macitentan caused LV hypertrophy regression independent of blood pressure changes in HFpEF. Although macitentan did not modulate diastolic dysfunction in HFpEF, it significantly reduced wall thickness and relative wall thickness after 2 weeks of therapy. In vitro studies showed that macitentan decreased the aldosterone-induced cardiomyocyte hypertrophy. These changes were mediated by a reduction in the expression of cardiac myocyte enhancer factor 2a. Moreover, macitentan improved adverse cardiac remodeling, by reducing the stiffer cardiac collagen I and titin n2b expression in the left ventricle of mice with HFpEF. Conclusions—: These findings indicate that dual ET-A/ET-B receptor inhibition improves HFpEF by abrogating adverse cardiac remodeling via antihypertrophic mechanisms and by reducing stiffness. Additional studies are needed to explore the role of dual ET-1 receptor antagonists in patients with HFpEF. Abstract : Supplemental Digital Content is available in the text.